What ales the earl - MacKenzie, Sally (Zebra historical romance., 2018)
When Penelope Barnes arrived at the Home with her young daughter, she discovered a knack for horticulture<U+2014>and for cultivating the hops needed to produce a superlative pint. She put her scandalous affair with Harry Graham firmly in the past, along with the wrenching pain she felt when he went off to war. After all, she<U+2019>d always known a farmer<U+2019>s daughter had no future with an earl<U+2019>s son. Now she has the pleasant memory of their passion, and she has little Harriet, for whom she would do anything<U+2014>even marry a boring country vicar . . . Harry went off to fight for the Crown unaware that his delightful interlude with his childhood friend had permanent consequences. Now he<U+2019>s back in England, catapulted into the title by his brother<U+2019>s untimely death. He sorely misses his former life of unfettered adventure, so when he has reason to explore Little Puddledon, he jumps at the chance. But what he finds there is something<U+2014>and someone<U+2014>he never knew he<U+2019>d lost, and a once forbidden love whose time has come, if only he can persuade Pen he<U+2019>s home to stay . . .